Retrospective analysis of hemophilia B in Turkey: identifying main characteristics and treatment options - Bülent Zülfikar; Başak Koç; Fahri Şahin; Hatice İlgen Şaşmaz; Kaan Kavaklı; Can Balkan; Ali Bülent Antmen; Sinan Akbayram; Birol Güvenç; Vahap Okan; Emine Türkkan; Canan Albayrak; et al. (Research and Practice in Thrombosis and Haemostasis)
Background: Hemophilia B (HB), an X-linked recessive inherited bleeding disorder, exhibits a high prevalence among males. Objectives: To present the first national cohort of persons with HB to define the demographics, clinical characteristics, and treatment patterns in Turkey. Methods: This multicenter, retrospective study included 433 alive persons with HB registered in 35 centers between 1961 and 2018. Analyses were performed by age subgroups (0-17 years, 18-64 years, and ≥65 years), disease severity by factor levels (severe, <1 IU/dL; moderate, 1-5 IU/dL; mild, >5 IU/dL). Additionally, patients were stratified based on the initiation year of follow-up at the relevant study center, creating 2 periods: 1993-2006 (referred to as period A) and 2007-2018 (referred to as period B). Results: Predominantly male (98.6%), the median age at data entry was 22.1 years (n = 429). The majority (49.0%) had moderate HB, followed by severe (30.0%) and mild (15.7%) disease. Of the 377 patients with complete treatment details, 209 (55.4%) were under prophylaxis from their diagnosis onwards, while 79 patients (21.0%) only received on-demand treatment. Additionally, 89 patients (23.6%) initially underwent on-demand treatment and later were switched to prophylaxis. Knees were the primary site of bleeding and the most frequently intervened joints. Most of the major (47.5%) and minor (53.3%) orthopedic procedures were carried out in persons with severe HB, while half of radioactive synovectomy procedures were performed on persons with moderate HB. Conclusion: This paper describes the demographics, clinical characteristics, and treatments patterns of a large cohort of alive persons with HB on a national scale.